Perkembangan Akuntansi Thailand dan Analisis Shenanigans pada Perusahaan Group Lease - Natalis Christian; Veronica Veronica; Lisa Lim (Politeknik Ganesha Medan, 2021)
Thailand is ASEAN country that managed to escape colonialism. However, like Anglo American countries, the country's accounting system emphasizes the transparency and information needs of investors. After the 1997 financial crisis, Thailand reformed to improve government cooperation and investment competition. Thailand's economy is recovering rapidly and is showing good growth. Due to economic growth, the poverty rate also fell. There are types of Thai state accounting standards namely International Financial reporting standards (IFRS) and Thai accounting standards (IFAC). The current development of accounting has to do with manipulation in the company's financial statements. A financial shenanigan is a false statement about the status and financial performance in a financial statement. Financial fraud can be a minor violation, such as through the free interpretation of accounting principles where it has 7 categories of shenanigans. In this discussion, the author presented an analysis of accounting progress in Indonesia with Thailand and analyzed 7 shenanigans to manipulate financial statements in Thai state companies. In this article take the company that makes the selected object that is the Group Lease company. This Group Lease is one of the companies originating from Thailand which is engaged in financing services. This method of research shows that group lease companies manipulate shenanigans 2.